Skin disorders in renal transplant recipients: a retrospective study - Pedro Miguel Clemente Garrido; João Borges-Costa (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Background: Immunosuppressive therapy, which is necessary to avoid graft rejection in renal transplant recipients, presents an increased risk of several pathologies, namely infectious and neoplastic. Objectives: To identify the most frequent skin diseases and their clinical and demographical risk factors within a population of renal transplant recipients. Methods: A retrospective study of renal transplant recipients referred to dermatology visit and observed for the first time from January 2008 to December 2014. Results: The study included 197 patients, 120 men (60,9%). Mean age was 50,7 years (±13,4). 12 patients (6,1%) had previous skin cancer. Infections were the most frequent reason of referral (93/197; 44%). From the total referred, 18,3% (36/197) presented pre-cancerous lesions. Malignancy was diagnosed in 36 patients (18,3%), with 29 non-melanoma skin cancers (14,7%) and 7 Kaposi sarcomas (3,6%). Ratio of basal cell carcinoma to squamous cell carcinoma was 1,1:1. Non-melanoma skin cancer was significantly associated with older age (p = 0,002), male gender (p = 0,028), history of previous skin cancer (p = 0,002) and higher duration of immunosuppressive therapy (p<0,001). Study limitations: Retrospective study, with data from the first visit in dermatology. We didn't made classification on skin-types. Conclusions: The great incidence of cutaneous infections and skin cancer is responsible for a significant morbidity. It is important to assure the regular dermatological follow-up of renal transplant recipients, which will promote the prevention, an early diagnosis and an efficient treatment.